MODERN INTEGRATION OF FOLK MEDICINE IN STOMACH AND ABDOMINAL PAIN (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article analyzes the scientific basis for the integration of folk medicine methods with modern medical approaches in the treatment of stomach and abdominal pain. The study used historical, content and comparative analysis methods, as well as expert questionnaires and statistical processing methods. The results show that the combination of phytotherapy, diet, massage and physiotherapy methods with modern clinical treatment provides high efficiency in reducing pain, alleviating symptoms and improving the general condition of patients. Also, the integrated approach serves to improve the quality of medical services, ensure economic efficiency and preserve the national medical heritage.